Emotions, intentionality, and practical rationality the contrast between the theories of emotions of William James and Antonio Damasio (2019)
The article presents and discusses the theories of emotions of W. James and A. Damasio, with emphasis on the intentionality of emotions and their connection with practical rationality. It argues that James' proposal encounters several difficulties in accounting for both aspects of emotions, and shows how Damasio's neo-Jamesian theory partly overcomes some of those difficulties, while giving rise to other objections. Finally, it summarizes Jesse Prinz's proposal regarding emotions as “embodied appraisals”, which seeks to combine the cognitive aspect and the corporeal nature of emotions. © 2019 Universidad Nacional de Colombia. All rights reserved.